Qualitative methods of performance evaluation in football - Cusano, P.; Rosa, R. (Sport Science - International Scientific Journal of Kinesiology, 2020)
Monitoring the behavior of an athlete or a team can also be developed through an objective data analysis of a sports performance, and is methodologically framed in the context of the performance analysis. In a specific sports competition it is possible to determine a series of specific factors through quantitative and qualitative methods, which may predict the outcome of the competition itself. New reference models are being developed, called Expected Score, which are used for the qualitative analysis of what happens during the dynamics of the football game, from which useful interdependencies with the final result can arise. The elements of the analysis are identified by means of different types of probability measures, aimed at identifying the most statistically useful constants for a sport-specific evaluation of the performance capacity of a team, such as offensive or defensive capacity indexes. These evaluations reveal some significant data on the athletes' performance related to the competition, and may predict its result.